Potentials of Hydrogel in Tissue Engineering: An Overview - Vijay, Bindu (Asian Journal of Pharmaceutics (AJP), 2024)
Over the years, the demand for tissue and organs has grown due to accidents and other disease conditions. Tissue repair and restoration are vital for maintaining the body’s integrity. However, the biggest challenge in tissue damage and repair has been finding an alternative cell/tissue for damage repair. Tissue engineering has proven successful in this field. Its primary objective lies in the creation of synthetic alternatives that bear close resemblance to natural tissues. Today, tissue regeneration from synthetic alternatives is successfully considered for treating several types of tissue damage and repair, including chronic kidney disease. This paper aims to give an overview of tissue engineering, emphasising hydrogel as a potential biomaterial for tissue engineering.